Lamborghini : the man behind the legend [videorecording (DVD)] - Moresco, Robert; Grillo, Frank, 1963-; Reggiani, Romano; Leoni, Matteo; Antonacci, Giovanni (Lionsgate, 2022)
It tells the story of genius auto inventor Ferruccio Lamborghini. All his life, Ferruccio has dreamed of beating his longtime rival Enzo Ferrari and the upcoming Geneva Grand Prix could be his chance to blow past Ferrari for good. But can Ferruccio get his untested vehicle prepped for victory with the competition just a month away? The race is on!